Introduction to Special Issue: Mobile technologies and inclusive development in Africa - Simplice Asongu; Agyenim Boateng (African Governance and Development Institute (AGDI), 2018)
The primary objective of this special issue is to showcase high-quality interdisciplinary research in the field of mobile phone technology and inclusive economic development, with a view to inspire and educate readers and policy makers on the vital role of mobile phones in economic development in Africa. We hope that the articles in this special issue will encourage academics and policy makers to carry out more research on the challenges and opportunities mobile phone technology offers in our quest to develop our communities.
Keywords: 330